REVISITING THE IMPACT OF FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH IN THAILAND - Yi- Syen Chong; Mui-Yin Chin (Tra Vinh University Journal of Science, 2022)
Past studies have researched how foreign direct investment has played a pivotal role in stimulating Thailand’s economic growth. However, Thailand’s foreign direct investment inflows have exhibited huge fluctuations from 1979 until now. Empirical studies have revealed that foreign direct investment worsens and weakens current accounts, raising foreign debt. In addition, foreign firms with large influence on market shares might crowd out domestic investment. Hence, this study aimed to re-examine the impact of foreign direct investment on Thailand’s economic growth in both the short and long run by employing yearly data from 1980 to 2019 using the Vector Error Correction Model and Granger Causality test. Besides, this study also investigated the impact of other determinants of economic growth, namely real effective exchange rate and trade. The empirical results revealed that foreign direct investment has positively impacted Thailand’s economy in the long run. In addition, foreign direct investment emerged as the most influential variable on economic growth. Given the importance of foreign direct investment for Thailand, The Board of Investment of Thailand should implement effective policies and provide incentives that benefit foreign investors to invest in the country. In addition, the government should implement further intervention measures to improve the positive spillover effects from foreign direct investment.